2019
DOI: 10.1016/j.jpha.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of twenty-five compounds in different parts of Astragalus membranaceus var. mongholicus and Astragalus membranaceus by UPLC-MS/MS

Abstract: As a traditional Chinese medicine, the root of Astragalus membranaceus var. mongholicus (AMM) or A. membranaceus (AM) has been widely used in China and other Asian countries for thousands of years. Till now, the flavonoids, phenolic acids and saponins are considered as the main active components contributing to their therapeutic effect in these plants. In order to clarify the distribution and contents of these compounds in different organs of these plants, a rapid and sensitive analytical method for simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 25 publications
(32 reference statements)
2
37
0
Order By: Relevance
“…Nonetheless, there was a common trend of the highest isoflavonoid accumulation in the root. The tendency of active secondary compound accumulation in A. mongholicus is consistent with what has been reported previously [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, there was a common trend of the highest isoflavonoid accumulation in the root. The tendency of active secondary compound accumulation in A. mongholicus is consistent with what has been reported previously [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a common trend that the four iso avonoids especially accumulate in roots. This tendency to accumulate active secondary compounds in A. mongholicus is consistent with previous reports [43][44]. To reveal the relationship between the iso avonoid biosynthesis and accumulation in different plant organs of A. mongholicus, candidate genes responsible for the iso avonoid biosynthesis must be identi ed and characterized in the biosynthetic pathway.…”
Section: Discussionsupporting
confidence: 87%
“…Flowers (6.96 mg GAE/g) and roots (6.03 mg QE/g) had the lowest level of total phenolics and flavonoids, respectively. Several studies reported different levels of these compounds in the members of the genus Astragalus [ 16 , 37 , 38 , 39 ]. Observed differences may be linked with geographical, environmental, and climatic conditions as well as plant parts [ 37 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%